The effect of technical competence in balance elements of rhythmic gymnastics on the sportive success of taekwondo Poomsae athletes - Polat, S. C. (Journal of Education and Training Studies, 2018)
This study aims to investigate the effect of technical competence in certain balance elements, an important parameter in rhythmic gymnastics, on sportive success in taekwondo poomsae athletes and the relationship between them. The study was conducted on 12 female taekwondo athletes (age: 17.6±1.2; height: 159.26±3.1 cm; weight: 50.79±1.82 kg; BMI: 20.88±0.98 kg/m2). The participants were selected from successful athletes who were in the top 6 in their own category in the national taekwondo competition held this year. The athletes performed 6 balance elements in rhythmic gymnastics, i.e. side passé (SP), 90° forward (90°F), side split with hand support (SSWHS), Arabesque with trunk forward (A), Cossack (C) and free leg to the side (FLS), and the Y balance test. The relationship between these balances that were assessed by 3 international judges and success rating was identified using the Spearman correlation test. The level of significance was accepted as p<0.05. As result, a statistically significant difference was found between side passé and split with hand support, balances used in rhythmic gymnastics, and success ratings (p<0.05). While no statistically significant difference was found between other balances, i.e. 90° forward, arabesque with trunk forward, cossack and free leg to the side and sportive success, there was a high relationship between them. In addition, there was no statistically significant difference between sportive success and right and left anterior (RAB, LAB) posteromedial (RPMB, LPMB) and posterolateral (RPLB, LPLB) reach distances. In conclusion, since the study found a high relationship between sportive success and technical competence of poomsae athletes in the two technical side balances, it is suggested that basic gymnastics training can be effective in improving the balancing skills of taekwondo poomsae athletes.